Iterative Synthesis of Edge-Bent [3]Naphthylene - Jin, Zexin; Teo, Yew Chin; Teat, Simon J.; Xia, Yan (Synlett, 2018)
Polycyclic conjugated hydrocarbons (PCHs) containing antiaromatic rings are of fundamental and technical interest. [N]naphthylene is an intriguing family of PCHs consisting of alternatingly fused naphthalenoids and antiaromatic cyclobutadienoids (CBDs). We recently reported the first three regioisomers of the [N]naphthylene family, synthesized by catalytic arene-norbornene annulation (CANAL) reaction followed by acidic aromatization. We now report an iterative strategy for CANAL synthesis allowing us to synthesize the forth regioisomer, edge-bent [3]naphthylene. The optoelectronic properties, local paratropicity, and crystal packing of the edge-bent [3]naphthylene were studied and compared with its closely related regioisomer, center-bent [3]naphthylene.
Keywords: annulation; iterative synthesis; antiaromaticity; polycyclic conjugated hydrocarbons; [3]naphthylene